Introducing Tempeh as a New Plant-Based Protein Food Item on the Danish Market - Margit Dall Aaslyng (MDPI AG, 2021)
Decreasing meat consumption has resulted in a need for new high-quality protein sources. Tempeh is relatively unknown in Denmark and might be capable of meeting this need. The aim of the study was to describe the success criteria for introducing locally produced tempeh and to investigate the sensory quality of three types of tempeh. Only 24% of the consumers in the survey (n = 395) used meat alternatives, which might be explained by a low level of satisfaction with availability. Tempeh was known by 26%—the less meat eaten, the greater the knowledge of tempeh. Twenty-three per cent of the consumers had positive attitudes towards tempeh. The three types of tempeh had markedly different sensory profiles. Nevertheless, the home use test showed that they could be used interchangeably in different recipes. In addition, the consumers were more positive about recipes in which tempeh did not resemble meat compared with meat-inspired recipes. In conclusion, introducing locally produced tempeh on the Danish market is possible but would require further knowledge of the product. In addition, tempeh should be sold as a tasty, high-quality protein food item in its own right. Recipes using tempeh should reflect this and not mimic meat recipes.